Fabrication and CO2 capture performance of magnesia-stabilized carbide slag by by-product of biodiesel during calcium looping process. (15th April 2016) - Ma, Xiaotong; Li, Yingjie; Shi, Lei; He, Zirui; Wang, Zeyan
Graphical abstract: Highlights: Novel CO2 sorbent is produced by carbide slag, Mg(NO3 )2 and by-product of biodiesel. By-product of biodiesel addition in production of novel sorbent improves CO2 uptake. The optimal mass ratio of CaO to MgO in the novel sorbent is 80:20. Novel sorbent consists of CaO–MgO grain groups and shows high CO2 capture capacity. Novel CO2 sorbent shows more porous structure than carbide slag in cycles. Abstract: A novel magnesia-stabilized carbide slag (MSCS) was synthesized with carbide slag, magnesium nitrate hydrate and by-product of biodiesel by combustion, which was used as a CO2 sorbent during the calcium looping process. The effects of preparation condition (combustion temperature, combustion duration, by-product of biodiesel addition and magnesia addition) and CO2 capture condition (carbonation and calcination atmosphere) on CO2 capture capacity of MSCS were investigated during the calcium looping cycles. The main compositions of MSCS are CaO and MgO. The addition of by-product of biodiesel in the preparation of the sorbent leads to the uniform mix of MgO and CaO grains in MSCS, which shows an obviously positive effect on its CO2 capture capacity. Only on the condition of the addition of by-product of biodiesel, MgO derived from magnesium nitrate hydrate improves the cyclic CO2 capture capacity and durability of MSCS during the multiple cycles. MSCS with a mass ratio of CaO to MgO of 80:20 combusted at 850 °C for 60 min exhibits higher CO2 capture capacity and greater durability. The CO2 capture capacity of MSCS can retain 0.42 g/g after 20 cycles, which is 60% higher than that of carbide slag. MSCS calcined under the high concentration of steam displays much higher CO2 capture capacity and better sintering resistance during the cycles, compared to MSCS calcined under the high concentration of CO2 . The addition of steam in the carbonation enhances CO2 capture capacities of MSCS and carbide slag. MSCS consists of CaO–MgO grain groups and the support of MgO sustains the high sintering resistance of the sorbent. MSCS remains much larger surface area and pore volume than carbide slag during the cycles, compared to carbide slag. MSCS appears promising as an effective and low-cost CO2 sorbent during the calcium looping.